2016
DOI: 10.1021/acs.bioconjchem.6b00246
|View full text |Cite
|
Sign up to set email alerts
|

Helix12-Stabilization Antagonist of Vitamin D Receptor

Abstract: To develop strong vitamin D receptor (VDR) antagonists and reveal their antagonistic mechanism, we designed and synthesized vitamin D analogues with bulky side chains based on the "active antagonist" concept in which antagonist prevents helix 12 (H12) folding. Of the synthesized analogues, compounds 3a and 3b showed strong antagonistic activity. Dynamic hydrogen/deuterium exchange coupled with mass spectrometry (HDX-MS) and static X-ray crystal structure analyses indicated that compound 3a stabilizes H11-H12 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 41 publications
5
44
0
Order By: Relevance
“…Due to weak affinity for corepressor peptides 13 or non-optimal crystal packing, only crystals of the complex in the presence of the SRC1 coactivator peptide NR2 (RHKILHRLLQEGS) were obtained and analyzed (Supplementary Table 1). These results are in agreement with previous reports characterizing X-ray structures of VDR complexes in presence of antagonist ligands [14][15][16][17][18][19] . ZK168281 binds to the VDR LBP unambiguously as shown by the POLDER omit map (Figure 1B).…”
Section: Binding Mode Of Zk168281 To Zvdr Lbdsupporting
confidence: 93%
“…Due to weak affinity for corepressor peptides 13 or non-optimal crystal packing, only crystals of the complex in the presence of the SRC1 coactivator peptide NR2 (RHKILHRLLQEGS) were obtained and analyzed (Supplementary Table 1). These results are in agreement with previous reports characterizing X-ray structures of VDR complexes in presence of antagonist ligands [14][15][16][17][18][19] . ZK168281 binds to the VDR LBP unambiguously as shown by the POLDER omit map (Figure 1B).…”
Section: Binding Mode Of Zk168281 To Zvdr Lbdsupporting
confidence: 93%
“…Comparatively, passive antagonists tend to fit into the ligand-binding pocket but facilitate repositioning of H12 to a stable but non-active configuration. A third mechanism of receptor antagonism has also been proposed where antagonists can facilitate H12 stabilization but destabilize other regions of the receptor including the dimerization interface, impeding the ability to form productive heterodimers with RXR 50 . It is worth noting however that non-competitive VDR antagonists have also been identified that function through disruption of VDR-coregulator interactions 51 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that several ligands also barely regulate VDR function . The bulky group in the adamantane compounds protrudes into the ligand‐binding pocket formed by the N‐terminal helix H3, the H6–H7 loop, helix H11, and the H11–H12 loop, leading to the expansion of the pocket (Fig.…”
Section: Discussionmentioning
confidence: 99%